Nigeria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This paper presents a simple structural model of inflation adapted for Nigeria based on the methodology of Berg, Karam, and Laxton. This approach allows different policy options to be considered systematically in a baseline forecasting exercise. The development and calibration of this model are ongoing. The consolidation of the banking system has transformed Nigeria's financial system and created opportunities for financial institutions and market participants; but, it also poses challenges for financial stability. Efforts must therefore be stepped up to strengthen supervision and regulatory interventions.